Macroeconomic Determinants And Stock Market Volatility: Evidences From Indian Stock Market - Vijay Kumar , Bishwajeet Prakash, Ankit Srivastava, Neha Rajput (International Journal of Advanced Science and Technology, 2020)
The study investigates the relationship of macroeconomic determinants (Exchange rate, Index of industrial production, Inflation and Broad money supply) on Indian Stock Exchange (BSE Sensex) by using monthly data over the period of April 2012 to August 2019. The research analysis is based on the following time series analysis techniques i.e. unit root test, cointegration analysis, impulse response function, variance decomposition analysis and granger causality test. The Augmented Dickey-Fuller unit root test has been applied to transform data series into stationary property while the Johansens cointegration technique has been applied which confirms the presence of long run relationship among the variables. The result of Impulse response function show that Exchange rate, Inflation and Money supply does not have any significant impact on stock market index while Index of industrial production shows positive impact on stock market index in India in both short run and long run. The result also confirms that maximum shock in stock market is due to their fluctuation.  The result of the Variance decomposition result shows that highest influence on stock market is recorded by Index of industrial production is 10.21 % in long run time period while the other macroeconomic determinants has very less influence on stock market in India. The result of the granger causality test further validate the result of Impulse response function and Variance decomposition analysis that Index of industrial production affect stock market index while Exchange Rate, Inflation & Money Supply does not affect Stock Market index. Thus the outcome of the study indicates that all these macroeconomic determinants have certain effect on stock market index in both short run and long run but Index of industrial production affects largely to Stock market index in India.